Occupational brucellosis in a veterinary assistant following exposure during management of bovine dystocia: a case report - Nagabhushanarao, Bhavana Venkata; Yesaswani, Reddy; Likhitha, Hariyala; Gayatri, Mekhala (International Journal of Research in Medical Sciences, 2025)
Brucellosis remains a significant occupational zoonosis in India, particularly affecting workers in the veterinary and livestock sectors who frequently interact with infected animals and reproductive tissues. The disease is caused by gram-negative intracellular coccobacilli of the genus Brucella, with B. abortus being the predominant species associated with bovine brucellosis. Veterinary personnel performing high-exposure procedures such as dystocia management, placentectomy and handling of aborted materials face the greatest risk due to the heavy bacterial load present in reproductive tissues. We describe a case of acute brucellosis in a 34-year-old veterinary assistant who developed undulant fever, arthralgia, generalized myalgia, malaise and sacroiliac pain after unprotected exposure to reproductive secretions during manual management of bovine dystocia in a herd experiencing multiple late-term abortions. Herd screening revealed widespread Brucella abortus positivity. Initial evaluation showed leukopenia and a false-positive Widal test, leading to misdiagnosis as enteric fever. Persistent fever and musculoskeletal symptoms led to further investigation, and Brucella IgM ELISA returned strongly positive, confirming acute infection. The patient received WHO-recommended therapy with doxycycline and rifampicin for six weeks, resulting in full recovery without relapse over three months of follow-up. This case highlights the occupational risks faced by veterinary personnel, diagnostic challenges caused by nonspecific symptoms and serological cross-reactivity, and the critical need for strengthened biosafety practices and One-Health–oriented surveillance systems to reduce the burden of brucellosis in endemic regions.